Flow of heterotrophic production in oligotrophic ocean waters - Alothman, Afrah; Duarte, Carlos M.; Qurban, Mohammed Ali; Agustí, Susana (Frontiers in Microbiology, 2025)
In oligotrophic ecosystems, bacterial production (BP) via the microbial loop and grazing processes plays a crucial role in carbon transfer (CT) to higher trophic levels. However, there studies quantifying CT from bacteria to the marine food web are limited. In this study, we used 13C-isotope tracers and cavity ring-down spectroscopy to measure primary production (PP), BP, bacterial respiration (BR), and CT within the microbial food web in oligotrophic waters. Our results revealed that the BP rate, ranging from 0.02 to 4.93 μg C L−1 d−1, was significantly lower than the total PP, which ranged from 2.69 to 16.71 μg C L−1 d−1. Our findings indicate that grazing of bacteria in the Red Sea is substantial. The removal of grazers through prefiltration lead to a 9.5-fold increase in BP rates, rising from 0.37 ± 0.04 μg C L−1 d−1 to 3.52 ± 1.04 μg C L−1 d−1 at the stations analyzed. This significant increase suggests that a large portion of bacterial carbon is rapidly transfer to higher trophic levels via grazing. In addition, carbon transfer (CT) to the food web, measured in size fractions above picoplankton (>1.2 or > 3 μm), accounted for an average of 72.7 ± 4.0% of the net bacterial production (Net BP = BP + CT), underscore the crucial role of grazers in bacterial carbon cycling. This transfer increased significantly with increasing temperatures, highlighting the enhanced role of the microbial loop in CT during warmer conditions. We found that at some stations, a large proportion of the carbon assimilated by bacteria was used for respiration, averaging 1.37 ± 0.54 μg C L−1 d−1. This high respiratory demand of bacterial cells in oligotrophic waters may explain the low bacterial growth efficiency (BGE) of 9.7% ± 1.0% observed in our study, along with the significant correlation between BP and BGE. Our findings demonstrated that BP effectively transfers carbon through the microbial loop to higher trophic levels in the oligotrophic and warm waters of the Red Sea.